2013
DOI: 10.1002/ijc.28086
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐138 suppresses ovarian cancer cell invasion and metastasis by targeting SOX4 and HIF‐1α

Abstract: Metastasis is the major factor affecting patient survival in ovarian cancer. However, its molecular mechanisms remain unclear. Our study used isogenic pairs of low-and high-invasive ovarian cancer cell lines to demonstrate the downregulation of miRNA-138 in the highly invasive cells, and its functioning as an inhibitor of cell migration and invasion. An orthotopic xenograft mouse model further demonstrated that the expression of miRNA-138 inhibited ovarian cancer metastasis to other organs. Results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(161 citation statements)
references
References 44 publications
(90 reference statements)
8
152
0
1
Order By: Relevance
“…Yang et al (26) found that miR-138 expression resulted in a significant inhibition of colorectal cancer cell migration and invasion in vitro and in vivo. In ovarian cancer, miR-138 overexpression repressed cancer cell invasion and metastasis (24). In nasopharyngeal carcinoma, miR-138 markedly decreased cell proliferation and colony formation in vitro, and tumorigenesis in vivo (37).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (26) found that miR-138 expression resulted in a significant inhibition of colorectal cancer cell migration and invasion in vitro and in vivo. In ovarian cancer, miR-138 overexpression repressed cancer cell invasion and metastasis (24). In nasopharyngeal carcinoma, miR-138 markedly decreased cell proliferation and colony formation in vitro, and tumorigenesis in vivo (37).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA is a kind of endogenous small non‐coding RNAs that could participate in many biological processes, including cell proliferation, apoptosis, cell differentiation and development 9, 16, 17, 25. It is believed that the dysregulation of miRNAs is closely related to the development and progression of a number of cancers 4, 5, 12, 13, 21.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have been reported to regulate different properties of cancers, such as cancer cell proliferation, migration, invasiveness, EMT, and so on, by repressing their target gene expression 5, 8, 16, 17, 18. Recent evidences indicate that several miRNAs have been involved in the tumorigenic driver pathways in NSCLC, which would be developed as a new therapeutic strategy of NSCLC 2, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Suppressing miR-138 aggravates the metastasis of ovarian cancer via activation of the LIM kinase 1 (Limk1)/cofilin signaling pathway. [66][67][68] By targeting histone family 2A variant, member X (H2AX), miR-138 is essential to regulate the DNA damage response in small cell lung cancer (SCLC) cells, the upregulation of which is responsible for the increased radiosensitivity of lung cancer. 69,70 MiR-138 plays roles not only in solid tumors, but also in chronic lymphocytic leukemia (CLL).…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%